Numerical investigation on material removal mechanism in elliptical vibration cutting of single-crystal silicon. (1st November 2021) - Liu, Changlin; Zhang, Jianguo; Zhang, Junjie; Chu, Jianning; Chen, Xiao; Xiao, Junfeng; Xu, Jianfeng
Abstract: Elliptical vibration cutting (EVC) is a promising technique for improving the cutting performance of single-crystal silicon. Whereas the material removal mechanism in the tool vibration cycle has not been adequately explored. In this paper, molecular dynamics simulation is carried out via a modified model to explore the material removal mechanism in EVC of single-crystal silicon. The tool vibration amplitude and nominal depth of cut in the simulation model is remarkably increased to describe the transient material removal feature in a single vibration cycle. A model of the effective tool rake angle is established to determine the dominant material removal mechanism. Furthermore, the influence of the tool edge radii, speed ratios, and vibration amplitudes on the extrusion to shear transition is studied. The results indicate that the dominant material removal mechanism shifts from the extrusion to shear in a single vibration cycle. Besides, based on the stress analysis, the formation mechanism of the subsurface damage in extrusion and shear stage is different. Furthermore, the extrusion to shear transition can be influenced by varying the geometry and vibration parameters while the critical value of the effective tool rake angle for the extrusion to shear transition is approximately identical. Highlights: The transition of the material removal mechanism in one vibration cycle of EVC was studied based on a modified model. The dominant factor for subsurface damage formation in one vibration cycle was investigated. The critical effective tool rake angle for extrusion to shear transition in EVC the was revealed. The influence of the tool edge radii, speed ratios and vibration amplitudes on material removal mechanism was explored.